Introduction - Desai,SR (2006)
In the United Kingdom well over 30,000 new cases of lung cancer are diagnosed each year and there are a roughly similar number of deaths attibutable to the disease annually. In recent years there has been a paradigm shift in emphasis in the management of patients with lung cancer: a ‘team approach’ is now considered most appropriate and most institutions now have dedicated groups of multidisciplinary specialists who contribute to clinical management. This multidisciplinary approach is reflected in the present volume dedicated to lung cancer. Individual chapters focus on the clinical aspects, pathology, radiology (including screening, diagnosis of symptomatic cases and staging) and treatment options in lung cancer. Because of the recent interest in the potential role of positron emission tomography for a variety of malignancies, a separate chapter is devoted to this technique. Whilst the volume is primarily directed at radiologists, it is hoped that the volume will also be of value to other medical specialists who regularly manage patients with lung cancer.